Strategies to improve the health of adolescent girls: adolescents are empowered in preventing stunting - Yuniarti; Zakiah; Niken Pratiwi (LPPM Politeknik Sandi Karsa, 2025)
Community service activities at the Integrated Service Post for Teenage Girls in Tabukan Raya Village, Tabukan Subdistrict, involved 10 cadres and 17 teenage girls. The event was opened by the Head of Village together with the managing midwife, village midwife, Family Empowerment and Welfare Organization, and cadres from the Integrated Service Post. The cadre training was conducted with pre-tests and post-tests to assess knowledge about adolescent girls' health, particularly the prevention of anemia, stunting, balanced nutrition, and healthy eating patterns. The results showed an increase in the cadres' knowledge about the risk factors for stunting, anemia, consumption of iron tablets, and nutritious foods. Knowledge plays a vital role in shaping health behavior (Lawrence Green's concept), and education is an effective strategy for changing the knowledge, attitudes, and behavior of adolescents. After the education, all cadres had good knowledge. The cadres are expected to be able to become health promotion agents and sources of information for their peers. The results of the adolescent girls' examination showed that there were still 12% with anemia, 47% underweight, 18% with chronic energy deficiency, and 35% short. Adolescence is a second window of opportunity to improve nutrition, as growth occurs rapidly. Anemia is a risk factor for stunting in early adolescent girls, so preventing anemia plays an important role in reducing stunting. Thus, empowering youth integrated service post cadres is a strategic alternative solution in improving adolescent health, especially in preventing stunting, as well as optimizing adolescent reproductive health